2012
DOI: 10.1007/s10886-012-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

High Conservatism in the Composition of Scent Gland Secretions in Cyphophthalmid Harvestmen: Evidence from Pettalidae

Abstract: The scent gland secretion of Austropurcellia forsteri was analyzed by gas chromatography–mass spectrometry, providing the first description of the secretion chemistry in the cyphophthalmid family Pettalidae. The secretion contained a total of 21 compounds: About 60% of the whole secretion consisted of a series of saturated, mono-unsaturated and doubly unsaturated methylketones, from C11 to C15, with a cluster of saturated and mono-unsaturated C13-methylketones dominating. A second fraction included several nap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 6 publications
4
18
0
Order By: Relevance
“…The identity of the compounds as NQ and MNQ, respectively, was underlined by RIs completely matching data from literature (RIs at 1421 and 1537 in Raspotnig et al 2012) and confirmed by comparison to the authentic compounds. Peaks G (M + at m / z 188) and H (M + at m / z 202) were proposed to be 2-methoxy-1,4-naphthoquinone and 2-methoxy-6-methyl-1,4-naphthoquinone, respectively.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The identity of the compounds as NQ and MNQ, respectively, was underlined by RIs completely matching data from literature (RIs at 1421 and 1537 in Raspotnig et al 2012) and confirmed by comparison to the authentic compounds. Peaks G (M + at m / z 188) and H (M + at m / z 202) were proposed to be 2-methoxy-1,4-naphthoquinone and 2-methoxy-6-methyl-1,4-naphthoquinone, respectively.…”
Section: Resultssupporting
confidence: 76%
“…In particular, 1,4-NQ and 6-MNQ have meanwhile been reported from cyphophthalmids of three different families hitherto analyzed (Raspotnig et al 2005, 2012) and at least exemplarily from phalangiid Eupnoi (Wiemer et al 1978) as well as from nemastomatid Dyspnoi (Raspotnig et al 2010). The finding of 1,4-NQ and 6-MNQ in Carinostoma further underlines the status of these compounds as ancestral characters of cyphophthalmid/palpatorean scent gland secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose that hydroquinones and their respective benzoquinones should be considered synonymous, if used for phylogenetic purposes. The identification of defensive compounds from the suborders Cyphophthalmi (Jones et al 2009;Raspotnig et al 2005Raspotnig et al , 2012 and Dyspnoi (Raspotnig et al 2010(Raspotnig et al , 2014bSchaider et al 2011) has allowed more precise inferences about the evolution of the defensive secretions in Opiliones (e.g., Raspotnig et al 2014a). As pointed out by these authors, knowing the biosynthetic routes of the defensive secretion is important because it allows a more realistic use of chemical data for phylogenetic purposes (e.g., proposing weight matrices).…”
Section: Discussionmentioning
confidence: 99%
“…5.2 ). These chelicerates do not synthesise silk or venom, but have evolved repugnatorial glands, which secrete acrid compounds including phenols (Raspotnig et al 2012 ). The cephalothorax of phalangid harvestmen bears a pair of median eyes, but lacks lateral eyes.…”
Section: Opiliones (Harvestmen)mentioning
confidence: 99%